Successional status, seed dispersal mode and overstorey species influence tree regeneration in tropical rain-forest fragments in Western Ghats, India. (7th August 2017) - Osuri, Anand M.; Chakravarthy, Dayani; Mudappa, Divya; Raman, T. R. Shankar; Ayyappan, N.; Muthuramkumar, S.; Parthasarathy, N.
Abstract: The effects of fragmentation and overstorey tree diversity on tree regeneration were assessed in tropical rain forests of the Western Ghats, India. Ninety plots were sampled for saplings (1–5 cm diameter at breast height (dbh); 5×5-m plots) and overstorey trees (>9.55 cm dbh; 20×20-m plots) within two fragments (32 ha and 18 ha) and two continuous forests. We tested the hypotheses that fragmentation and expected seed-dispersal declines (1) reduce sapling densities and species richness of all species and old-growth species, and increase recruitment of early-successional species, (2) reduce the prevalence of dispersed recruits and (3) increase influence of local overstorey on sapling densities and richness. Continuous forests and fragments had similar sapling densities and species richness overall, but density and richness of old-growth species declined by 62% and 48%, respectively, in fragments. Fragments had 39% lower densities and 24% lower richness of immigrant saplings (presumed dispersed into sites as conspecific adults were absent nearby), and immigrant densities of old-growth bird-dispersed species declined by 79%. Sapling species richness (overall and old-growth) increased with overstorey species richness in fragments, but was unrelated to overstorey richness in continuous forests. Our results show that while forest fragments retain significant sapling diversity, losses of immigrant recruits and increased overstorey influence strengthen barriers to natural regeneration of old-growth tropical rain forests.